Comprehending Suicide: Landmarks in 20th–century Suicidology.
DOI: 10.1037/10406-007
|View full text |Cite
|
Sign up to set email alerts
|

Man against himself.

Abstract: MENNINGER MAN AGAINST HIMSELFOriginally published in New York, 1938 Freud's two best salesmen in America were Benjamin Spock (whose book Baby and ChiZd Care sold more copies than any other book except the Bible) and Karl A. Menninger, America's avuncular all-American Kansas family psychiatrist. In a way, both men were baby doctors: Spock was the trustworthy pediatrician-it was said that all one needed to raise a child was a baby and a copy of Spock-and Menninger, who explained to America how childhood compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
13

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 0 publications
0
25
0
13
Order By: Relevance
“…24 It has been suggested that people "show less respect for tramways than for other types of transport," which may explain the higher frequency of unintentional injuries with tramways. 25 For subway suicide, which has been described as a highly aggressive suicide method involving a deep "wish to be murdered or overwhelmed," the reasoning may be the other way round: 26 The different train appearance, together with the outlined technical differences, may influence individuals who intend to die by subway suicide to choose the faster train type. Of note, differences with regard to behavior patterns shown in subway suicides and suicide attempts have repeatedly been discussed in the literature.…”
Section: Discussion Train Types Serving the Stationmentioning
confidence: 99%
“…24 It has been suggested that people "show less respect for tramways than for other types of transport," which may explain the higher frequency of unintentional injuries with tramways. 25 For subway suicide, which has been described as a highly aggressive suicide method involving a deep "wish to be murdered or overwhelmed," the reasoning may be the other way round: 26 The different train appearance, together with the outlined technical differences, may influence individuals who intend to die by subway suicide to choose the faster train type. Of note, differences with regard to behavior patterns shown in subway suicides and suicide attempts have repeatedly been discussed in the literature.…”
Section: Discussion Train Types Serving the Stationmentioning
confidence: 99%
“…This framework builds upon those proposed by Cooper (2006) in her analyses of the relation between AI and high-risk sexual behavior and from Menninger (1938) and Koob and colleagues (e.g., Koob & Le Moal, 1997), who have highlighted the importance of distinguishing between alcohol's acute and chronic effects on brain and behavior. As shown in Figure 1, this framework can be broadly construed to reflect the alcohol (A) and suicide (S) relation along two domains: (1) directionality, and (2) temporality.…”
Section: Part 1: Theoretical Frameworkmentioning
confidence: 99%
“…This association has been hypothesized since the birth of modern psychiatry. Menninger conceptualized addiction as both a protracted from of chronic suicide and as playing a part in focal deliberate "accidents" (Menninger, 1938). Similar to Menninger, we believe that alcohol can relate to suicide attempts both situationally and chronically, and the aim of this paper is to put forth a conceptual framework of the relation between AI and suicide attempts.…”
Section: Introductionmentioning
confidence: 99%
“…Menninger's dynamic point of view from 1938 [31] regarded self-mutilation as a morbid form of self help ''to avert total annihilation that is to say suicide''. Apart from the fact that he was the first researcher to place self-mutilation in the framework of psychoanalytic theory of defence mechanisms, he presented the first differentiation or contrast between suicide and self-injury.…”
Section: Introductionmentioning
confidence: 99%